Pemanfaatan Media Youtube oleh Guru PAI dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa SMP Negeri 4 Marangkayu Kutai Kartanegara - Arda, Muhammad; Rosadi, Khumaini (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
Abstract – This thesis discusses the efforts of Islamic Education teachers in improving the ability to read the Qur'an through the YouTube application among eighth-grade students of SMP Negeri 4 Marangkayu, Kutai Kartanegara. The research aims to describe (1) the efforts of Islamic Education teachers in enhancing the Qur'an reading skills of eighth-grade students at SMP Negeri 4 Marangkayu, Kutai Kartanegara, and (2) the improvement of Qur'an reading skills through the YouTube application among eighth-grade students at SMP Negeri 4 Marangkayu, Kutai Kartanegara. This type of research is qualitative, using data collection techniques such as observation, interviews, and documentation. The subjects of this research are the Islamic Education teachers of eighth grade at SMP Negeri 4 Marangkayu, Kutai Kartanegara. The results of this study indicate that: the efforts of Islamic Education teachers include (1) forming a BTQ program, (2) providing motivation, (3) providing guidance, (4) peer tutoring, (5) learning through the YouTube application. To improve the reading ability of the Al-Qur’an among students in grade VIII, the Islamic Education teacher conducts (1) grouping students based on their reading ability of the Al-Qur’an, (2) encouraging reading the Al-Qur’an before starting the lesson, (3) using appropriate methods, (4) providing memorization exercises for students who read the Al-Qur’an fluently and special Iqro lessons for those who are still learning the hijaiyyah letters. The efforts of the Islamic Education teacher to enhance the reading ability of the Al-Qur’an are very appropriate by using the YouTube application for the students of SMP Negeri 4 Marangkayu, Kutai Karta Negara.